AN APPLICATION OF HYPERGEOMETRIC FUNCTION ON CERTAIN CLASSES OF ANALYTIC FUNCTIONS - SINGH, Dr. BALVIR; PORWAL*, SAURABH (International Journal of Mathematical Archive, 2018)
The purpose of the present paper is to investigate some interesting criteria for hypergeometric functions belonging to classes Â and . We also studied an integral operator related to hypergeometric functions relevant connection of the results presented herewith various well known results are briefly indicated.